How does tunnel interior color environment influence driving behavior? Quantitative analysis and assessment experiment. (April 2020) - Qin, Xiaochun; Zhang, Nan; Zhang, Weihan; Meitner, Michael
Abstract: Altering the visual environment inside a tunnel will affect the driving behavior which relies on the tunnel environment. However, there have been few studies on the influence of the differences of the tunnel interior color environment on driving characteristics. In this study, five wall color decoration schemes were designed and quantified based the color landscape quantified theory. The effects of different color decoration schemes on driver's subjective feelings, the constant speed driving time and the lane offset were analyzed in the experiment to verify the impacts of color decoration of interior tunnel walls on improving driving behavior. 60 subjects were chosen to drive in the driving simulator with different color decoration schemes. Meanwhile, the landscape color quantification method was proposed and the information value of different schemes was calculated quantitatively by the method to collect subjective evaluation value, constant speed driving time and lane offset respectively. The results indicated that the driver's subjective evaluation and driving behavior were highly correlated with the environmental information of the tunnel. The driver's characteristics had an obvious improvement with the increase of environmental information by color decoration schemes. However, it was also found that excessive environmental information has the potential to cripple driver characteristics. Driving experience and gender of the drivers had no significant influence on the subjective evaluation and driving behavior under different schemes, which revealed that the color design could be used to increase the environmental information in the tunnel. The results of this study can be used to provide the references for improving the driving visual environment quality in tunnels and also the driving comfort and safety, which would help to guide the rational design of tunnel interior color environments.